Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure, let's differentiate the function [tex]\( f(x) = \ln \left(x^2 + 1\right) \)[/tex] step by step.
### Step 1: Define the function
The function we need to differentiate is:
[tex]\[ f(x) = \ln (x^2 + 1) \][/tex]
### Step 2: Apply the chain rule
To differentiate [tex]\( f(x) = \ln (g(x)) \)[/tex], where [tex]\( g(x) = x^2 + 1 \)[/tex], we use the chain rule. The chain rule states that:
[tex]\[ f'(x) = \frac{d}{dx}[\ln (g(x))] = \frac{1}{g(x)} \cdot g'(x) \][/tex]
### Step 3: Differentiate the inner function
Now, we need to find [tex]\( g'(x) \)[/tex] where [tex]\( g(x) = x^2 + 1 \)[/tex]:
[tex]\[ g(x) = x^2 + 1 \][/tex]
[tex]\[ g'(x) = \frac{d}{dx} [x^2 + 1] = 2x \][/tex]
### Step 4: Combine the results
Substitute [tex]\( g(x) \)[/tex] and [tex]\( g'(x) \)[/tex] back into the chain rule formula:
[tex]\[ f'(x) = \frac{1}{x^2 + 1} \cdot 2x \][/tex]
### Step 5: Simplify the expression
The derivative of the function [tex]\( f(x) \)[/tex] simplifies to:
[tex]\[ f'(x) = \frac{2x}{x^2 + 1} \][/tex]
So, the derivative of [tex]\( \ln (x^2 + 1) \)[/tex] is:
[tex]\[ \boxed{\frac{2x}{x^2 + 1}} \][/tex]
### Step 1: Define the function
The function we need to differentiate is:
[tex]\[ f(x) = \ln (x^2 + 1) \][/tex]
### Step 2: Apply the chain rule
To differentiate [tex]\( f(x) = \ln (g(x)) \)[/tex], where [tex]\( g(x) = x^2 + 1 \)[/tex], we use the chain rule. The chain rule states that:
[tex]\[ f'(x) = \frac{d}{dx}[\ln (g(x))] = \frac{1}{g(x)} \cdot g'(x) \][/tex]
### Step 3: Differentiate the inner function
Now, we need to find [tex]\( g'(x) \)[/tex] where [tex]\( g(x) = x^2 + 1 \)[/tex]:
[tex]\[ g(x) = x^2 + 1 \][/tex]
[tex]\[ g'(x) = \frac{d}{dx} [x^2 + 1] = 2x \][/tex]
### Step 4: Combine the results
Substitute [tex]\( g(x) \)[/tex] and [tex]\( g'(x) \)[/tex] back into the chain rule formula:
[tex]\[ f'(x) = \frac{1}{x^2 + 1} \cdot 2x \][/tex]
### Step 5: Simplify the expression
The derivative of the function [tex]\( f(x) \)[/tex] simplifies to:
[tex]\[ f'(x) = \frac{2x}{x^2 + 1} \][/tex]
So, the derivative of [tex]\( \ln (x^2 + 1) \)[/tex] is:
[tex]\[ \boxed{\frac{2x}{x^2 + 1}} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.